Proton pump inhibitors – their possible influence on the development of small intestine bacterial overgrowth in children - Wasielewska, Zuzanna; Krogulska, Aneta; Szaflarska-Popławska, Anna (Pediatria Polska - Polish Journal of Paediatrics, 2023)
Proton pump inhibitors (PPIs) are safe drugs that have been commonly used for many years by both general practitioners and specialists. They are widely used in the paediatric population, mainly in the treatment of gastroesophageal reflux disease, but also for oesophagitis, gastritis and/or duodenitis. Proton pump inhibitors use increases the pH of the stomach, which disrupts the physiological defensive barrier and may lead to the development of an abnormal microbiome in the further parts of the digestive tract, resulting in small intestinal bacterial overgrowth (SIBO) and symptoms such as diarrhoea, production of gas, nonspecific abdominal pain, flatulence, lack of growth or weight loss, protein or energy malnutrition, and vitamin A, D, K and B12 deficiency. The study analyses the influence of combining PPIs with probiotics or prokinetics on the chance of SIBO developing in children. There are currently no diagnostic standards or therapeutic guidelines for children diagnosed with SIBO.